Kaner biodiesel production through hybrid reactor and its performance testing on a CI engine at different compression ratios - Ashok Kumar Yadav; Mohd Emran Khan; Amit Pal (Egyptian Journal of Petroleum)
The present study deals with development of a hybrid reactor for biodiesel production based on the combined hydrodynamic cavitation and mechanical stirring processes. Biodiesel were produced using Kaner Seed Oil (KSO). The experimental results show that hybrid reactor produces 95% biodiesel yield within 45 min for 0.75% of catalyst and 6:1 M ratio which is significantly higher as compared to mechanical stirring or hydrodynamic cavitation alone. Thus biodiesel production process in hybrid reactor is cheap (high yield), efficient (time saving) and environmentally friendly (lower% of catalyst). Performance study on engine shows that an increase in compression ratios (from 16 to 18) improves the engine performance using biodiesel blends as compared to petroleum diesel.